A Therapeutic Approach in Communication for the Recovery of Child Victims of Sexual Abuse in Kasemen Sub-District, Serang City - Marthalena, Marthalena; Mulyasih, Rahmi; Santi, Endang Tri; Berthanila, Rethorika; Najmi, Muhammad (Future Science, 2024)
Child sexual abuse is a serious problem that requires a holistic approach in handling it. Sexual abuse is committed by the closest people such as family, teachers and neighbours of the victim. There is an impact or trauma experienced by child victims of sexual abuse, for example, they become more quiet and tend to close themselves. This study aims to explore the use of therapeutic communication as a tool to help child victims of sexual abuse in the recovery process. Qualitative methods were used to understand the experiences and perceptions of children traumatised by sexual abuse. Using the therapeutic communication approach, there are four stages to go through: pre-interaction, orientation, and problem solving, and resolution steps to get the best results. The results showed that therapeutic communication has an important role in reducing the psychological impact and helping children overcome trauma